ОПЫТ ПРИМЕНЕНИЯ ЛИНЕАМЕНТНОГО АНАЛИЗА ПРИ ИЗУЧЕНИИ ОСОБЕННОСТЕЙ РАЗМЕЩЕНИЯ СКОПЛЕНИЙ ГЛУБОКОВОДНЫХ СУЛЬФИДНЫХ РУД НА УЧАСТКЕ 12°58'С.Ш., СЕВЕРО- АТЛАНТИЧЕСКИЙ ХРЕБЕТ - Егоров И.В.; Андреев С.И. (My University, 2005)
The detailed bathymetric maps of the Middle Atlantic Ridge axis zone obtained by submarine stacked-beam sur-vey have let to fulfill the lineament analysis of the structural-tectonic position of abyssal sulfide-bearing ores. Recent hydrothermal activity and related sulfide-bearing ores were showed to gravitate to the most young fault system of di-agonal strike. These results may be helpful in sulfide ore prospecting.
Keywords: 551.4.012>551.462.62(261.1)